Counting the cost of carbon in bioenergy systems: sources of variation and hidden pitfalls when comparing life cycle assessments. Issue 6 (November 2011) - Rowe, Rebecca; Whitaker, Jeanette; Freer-Smith, Peter H; Chapman, Jennifer; Ryder, Stephen; Ludley, Kate E; Howard, David C; Taylor, Gail
Energy from biomass is renewable and capable of providing heat, power or liquid fuels. Life cycle assessments of these renewable fuels have often shown positive energy balances and GHG savings, relative to fossil fuels. There are, however, large variations between studies and not all are positive, leading to recent reports questioning the long-term sustainability of bioenergy. Using a systematic review of life cycle assessments relevant to feedstocks grown in a temperate climate (three for heat and power and eight for liquid biofuels) we have defined these sources of variation, highlighting areas of uncertainty and priorities for future research. In addition, we have explored the challenges in comparing bioenergy and biofuels production chains and their fossil fuel equivalents and demonstrated how this can be done in a fair and consistent manner.